Electrospun scaffolds limit the regenerative potential of the airway epithelium. Issue 4 (16th July 2019) - Schwartz, Cynthia M.; Stack, Jacob; Hill, Cynthia L.; Lallier, Scott W.; Chiang, Tendy; Johnson, Jed; Reynolds, Susan D.
Abstract : Objective: Significant morbidity and mortality are associated with clinical use of synthetic tissue‐engineered tracheal grafts (TETG). Our previous work focused on an electrospun polyethylene terephthalate and polyurethane (PET/PU) TETG that was tested in sheep using a long‐segment tracheal defect model. We reported that graft stenosis and limited epithelialization contributed to graft failure. The present study determined if the epithelialization defect could be attributed to: 1) postsurgical depletion of native airway basal stem/progenitor cells; 2) an inability of the PET/PU‐TETG to support epithelial migration; or 3) compromised basal stem/progenitor cell proliferation within the PET/PU environment. Study Design: Experimental. Methods: Basal stem/progenitor cell frequency in sheep that underwent TETG implantation was determined using the clone‐forming cell frequency (CFCF) method. A novel migration model that mimics epithelial migration toward an acellular scaffold was developed and used to compare epithelial migration toward a control polyester scaffold and the PET/PU scaffold. Basal stem/progenitor cell proliferation within the PET/PU scaffold was evaluated using the CFCF assay, doubling‐time analysis, and mitotic cell quantification. Results: We report that TETG implantation did not decrease basal stem/progenitor cell frequency. In contrast, we find that epithelial migration toward the PET/PU scaffold was significantly less extensive than migration toward a polyester scaffold and that the PET/PU scaffold did not support basal stem/progenitor cell proliferation. Conclusions: We conclude that epithelialization of a PET/PU scaffold is compromised by poor migration of native tissue‐derived epithelial cells and by a lack of basal stem/progenitor cell proliferation within the scaffold. Level of Evidence: NA